‘Teddy Bear Pharmacy’: An Interactive Game Module for Health Education by Pharmacy Students - Athirah Daud, Nur Aizati (International Journal of Human and Health Sciences (IJHHS), 2025)
Objective: Children often lack knowledge about healthy lifestyles, safe medication use, and the role of healthcare professionals, leading to unhealthy habits and misconceptions. To overcome this, Teddy Bear Pharmacy (TBP) is introduced by Persatuan Sains Farmasi, USM. TBP, inspired by the concept of ‘Teddy Bear Hospital’ organized by IMACATS, aimed at introducing children under 12 to healthy lifestyles, proper and safe medication use, health check-ups, and hygiene care. The module development was initiated in 2022, also aimed to provide a platform for pharmacy students to hone their communication skills in delivering public health information to children. Methods: The game module is role-play-based, where each child brings their teddy bear, acting as the “patient,” while the child assumes the role of the pharmacist. There are five stations, each featuring interactive mini-games and activities: registration, a health measurement station, a consultation with a pharmacist along with an exhibition of various medication dosage forms, a station on hygiene practices, and a station for engaging physical activities. In addition, the module introduces the role of pharmacists as healthcare professionals to children and dispels any negative perceptions they may have about pharmacies and medications. Pharmacy students conducted the program as part of six community events, both inside and outside the university. Result: To date, a total of 459 children have participated in TBP program. The available TBP module is complete with game instructions and materials needed. A copyright application for the TBP module is underway to ensure the quality of materials is maintained. Conclusion: The TBP module is an innovation in training communication skills among pharmacy students in early health education for children through a fun and innovative approach. Future collaboration with IMACATs may offer opportunities for interdisciplinary involvement, integrating pharmacy students with other healthcare disciplines to further enrich the learning experience. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S43